Tools for the Assessment of Comorbidity Burden in Rheumatoid Arthritis - Aslam, Fawad; Khan, Nasim Ahmed (Frontiers in Medicine, 2018)
Introduction: Comorbidities influence the prognosis, clinical outcomes, disease activity, and treatment response in rheumatoid arthritis (RA). RA patients have a high comorbidity burden necessitating their study. Comorbidity indices are used to measure comorbidities and to study their impacts on different outcomes. A large number of such indices are used in clinical research. Some indices have been specifically developed in RA patients. Aim: This review aims to provide an overview of generic and specific comorbidity indices commonly used in RA research. Methods: We performed a critical literature review of comorbidity indices in RA using the PubMed database. Results/Discussion: This non-systematic literature review provide an overview of generic and specific comorbidity indices commonly used in RA studies. Some of the older but commonly used comorbidity indices like the Charlson comorbidity index and the Elixhauser comorbidity measure were primarily developed to estimate mortality risk from comorbid diseases. They were not specifically developed for RA patients but have been widely used in rheumatology comorbidity measurement. Of the many comorbidity indices available, only the rheumatic disease comorbidity index and the multimorbidity index have been specifically developed in RA patients. The functional comorbidity index was developed to look at functional disability and has been used in RA patients considering that morbidity is more important than mortality in such patients. While there is limited data comparing these indices, available evidence seems to favor the use of rheumatic disease comorbidity index as it predicts mortality, hospitalization, disability and healthcare utilization. The choice of the index, however, depends on several factors such as the population under study, outcome of interest, and sources of data. More research is needed to study the RA specific comorbidity measures to make evidence based recommendations for the choice of a comorbidity measure.